Human Airway Smooth Muscle Cells Express the High Affinity Receptor for IgE (FcεRI): A Critical Role of FcεRI in Human Airway Smooth Muscle Cell Function - Gounni, Abdelilah Soussi; Wellemans, Vincent; Yang, Jia; Bellesort, Fabienne; Kassiri, Kamrouz; Gangloff, Sophie; Guenounou, Moncef; Halayko, Andrew J.; Hamid, Qutayba; Lamkhioued, Bouchaib (The Journal of immunology (1950), 2005)
Several reports suggest that activated airway smooth muscle (ASM) cells are capable of generating various proinflammatory mediators, including cytokines and chemokines. However, little is known about the mechanism involved in this process. In this regard, we have examined the expression and the role of the high affinity IgE receptor (FcεRI) by ASM cells. Human ASM cells were found to constitutively express transcripts coding for α, β, and γ subunits of FcεRI. Flow cytometry and Western blot analysis confirmed the expression of FcεRI α-chain protein. Interestingly, FcεRI α-chain immunoreactivity was also demonstrated in smooth muscle within bronchial biopsies of asthmatic subjects. Cross-linking of FcεRI induced mobilization of free calcium in ASM cells, one of the critical signals to trigger smooth muscle contraction. Furthermore, cultured ASM cells released IL-4, IL-13, IL-5, and eotaxin but not IFN-γ, when sensitized with IgE followed by anti-IgE Ab cross-linking. The addition of anti-FcεRI α-chain Abs directed against IgE binding site inhibited this release. Taken together, these results suggest a potential new and important mechanism by which ASM cells may participate in airway inflammation and bronchoconstriction associated with allergic asthma.